2016
DOI: 10.1038/srep36414
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial dendritic cells and sensory nerves are structurally associated and functional interdependent in the cornea

Abstract: The corneal epithelium consists of stratified epithelial cells, sparsely interspersed with dendritic cells (DCs) and a dense layer of sensory axons. We sought to assess the structural and functional correlation of DCs and sensory nerves. Two morphologically different DCs, dendriform and round-shaped, were detected in the corneal epithelium. The dendriform DCs were located at the sub-basal space where the nerve plexus resides, with DC dendrites crossing several nerve endings. The round-shaped DCs were closely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 49 publications
4
83
1
Order By: Relevance
“…7,14 A number of human and mouse studies have established a structural relationship between dendritic cells and corneal nerves, with current hypotheses suggesting that elevated DC density leads to changes in the corneal nerves, and subsequently, a disruption to corneal homeostasis. 27,41 Similar to our findings in mice, human studies have identified no significant change to corneal epithelial DCs with aging in a healthy population. 42 In the context of inflammation, numerous studies have highlighted a negative correlation between corneal nerves and DC density, suggesting a functional relationship between corneal nerve pathology and DC activation in the corneal epithelium.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…7,14 A number of human and mouse studies have established a structural relationship between dendritic cells and corneal nerves, with current hypotheses suggesting that elevated DC density leads to changes in the corneal nerves, and subsequently, a disruption to corneal homeostasis. 27,41 Similar to our findings in mice, human studies have identified no significant change to corneal epithelial DCs with aging in a healthy population. 42 In the context of inflammation, numerous studies have highlighted a negative correlation between corneal nerves and DC density, suggesting a functional relationship between corneal nerve pathology and DC activation in the corneal epithelium.…”
Section: Discussionsupporting
confidence: 89%
“…A smaller population of DCs also exist in the corneal stroma. 26,27 For clarity, reference to DCs in this present study will relate only to corneal epithelial DCs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of 5 light burns to the cornea likely results in multiple sources of chemokine and cytokine release and in turn, the multidirectional chemotactic migration seen in our results. Another likely confounding factor in the change in cell motility is the loss of corneal nerve fibers in these locations, with close proximity between CLs and corneal nerves having been reported in the steady-state cornea (27,79). Other inflammatory states, such as single epithelial injury or suture placement, resulting in a single source of chemokine release, will likely show directional chemotactic migration.…”
Section: Discussionmentioning
confidence: 99%